Distribution of C30 carotenoid biosynthesis genes suggests habitat adaptation function in insect-adapted and nomadic Lactobacillaceae - Tom Eilers; Marie Legein; Jari Temmermans; Jelle Dillen; Ine Vandendriessche; Koen Sandra; Peter A. Bron; Stijn Wittouck; Sarah Lebeer (Communications Biology)
Abstract Carotenoids are membrane-bound pigments that are essential for photosynthesizing plants and algae, widely applied in food, feed and cosmetics due to their antioxidant and anti-inflammatory properties. The production of carotenoids, particularly C30 forms, has been documented in some non-photosynthetic prokaryotes. However, their function, distribution and ecology beyond photosynthesizing organisms remains understudied. In this study, we performed an eco-evolutionary analysis of terpenoid biosynthetic gene clusters in the Lactobacillaceae family, screening 4203 dereplicated genomes for terpenoid biosynthesis genes, and detected crtMN genes in 28/361 (7.7%) species across 14/34 (41.2%) genera. These genes encode key enzymes for producing the C30 carotenoid 4,4′-diaponeurosporene. crtMN genes appeared to be convergently gained within Fructilactobacillus and horizontally transferred across species and genera, including Lactiplantibacillus to Levilactobacillus. The phenotype was confirmed in 87% of the predicted crtMN gene carriers (27/31). Nomadic and insect-adapted species, particularly those isolated from vegetable fermentations, e.g., Lactiplantibacillus, and floral habitats, e.g., Fructilactobacillus, contained crtMN genes, while vertebrate-associated species, including vaginal associated species, lacked this trait. This habitat association aligned with the observations that C30 carotenoid-producing strains were more resistant to UV-stress. In summary, C30 carotenoid biosynthesis plays a role in habitat adaptation and is scattered across Lactobacillaceae in line with this habitat adaptation.